Comparing acute effects of extra virgin coconut oil and extra virgin olive oil consumption on appetite and food intake in normal-weight and obese male subjects - Metin, Ziya Erokay; Bilgic, Pelin; Tengilimoğlu Metin, Mercan Merve; Akkoca, Muzaffer (PloS one, 2022)
The aim of this study is to compare acute effects of consuming extra virgin coconut oil (EVCO) as a source of medium chain fatty acids and extra virgin olive oil (EVOO) as a source of long chain fatty acids in normal weight and obese subjects. Randomised, crossover design. Metabolically healthy twenty male subjects (10 normal weight; 10 obese) aged 19-40 years. Subjects consumed breakfast meals containing skimmed milk, fat-free white cheese, bread and EVCO (25 g) or EVOO (25 g). Visual analog scale evaluations, resting metabolic rate measurements and selected blood parameters analysis (glucose, triglyceride, insulin and plasma peptide YY) were performed before and after the test breakfast meals. In addition, energy intakes were evaluated by ad libitum lunch meal at 180 min. Visual analogue scale values of hunger and desire to eat decreased significantly after EVCO consumption than EVOO consumption in normal weight subjects at 180 min. There was an increase trend in plasma PYY at 30 and 180 min after EVCO breakfast compared to EVOO breakfast. Ad libitum energy intakes after EVCO and EVOO consumption in normal weight subjects were 924 ± 302; 845 ± 158 kcal (p = 0.272), respectively whereas in obese subjects were 859 ± 238; 994 ± 265 kcal (p = 0.069) respectively. The results of this study shows that consumption of EVCO compared to EVOO may have suppressive effect on hunger and desire to eat, may affect postprandial PYY levels differently and have no effect on postprandial energy expenditure.